![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
图中第三题
3个回答
展开全部
f(x+1)-f(x)=2x且f(0)=1;
解:【1】
f(1)-f(0)=0
f(1)=1;
f(2)-f(1)=2
f(2)=3;
f(3)-f(2)=4
f(3)=7;
f(4)-f(3)=6
f(4)=13;
...........
f(x)=2的x幂-x
【2】在[-1,1]上f(x)>2x+m恒成立,则
f(-1)>m-2
f(1)>2+m
由【1】得
1/2>m-2
1>2+m
综述m<-1
解:【1】
f(1)-f(0)=0
f(1)=1;
f(2)-f(1)=2
f(2)=3;
f(3)-f(2)=4
f(3)=7;
f(4)-f(3)=6
f(4)=13;
...........
f(x)=2的x幂-x
【2】在[-1,1]上f(x)>2x+m恒成立,则
f(-1)>m-2
f(1)>2+m
由【1】得
1/2>m-2
1>2+m
综述m<-1
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询